2015
DOI: 10.1097/meg.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

AST/ALT ratio is not useful in predicting the degree of fibrosis in chronic viral hepatitis patients

Abstract: In conclusion, our data suggest that four of the five noninvasive methods evaluated in this study can be used to predict advanced fibrosis in patients with hepatitis B and C. However, there was no significant relationship between the degree of hepatic fibrosis and the AAR score, indicating that AAR is not useful in estimating the fibrosis stage in hepatitis B and C patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 23 publications
8
31
2
Order By: Relevance
“…The APRI model, which was first investigated by Wai et al in the staging of fibrosis among CHB patients, showed the most accurate diagnostic value and most powerful predictive value for fibrosis among the models in this study (19). The AUROC of APRI in the prediction of significant fibrosis was 0.688; this finding seems to be consistent with the data reported in the literature (20)(21)(22)(23)(24). The NPV of APRI in the prediction of fibrosis and cirrhosis was > 90% in a study by Guzelbulut et al and 92% in a study by Celikbilek et al (20,22).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The APRI model, which was first investigated by Wai et al in the staging of fibrosis among CHB patients, showed the most accurate diagnostic value and most powerful predictive value for fibrosis among the models in this study (19). The AUROC of APRI in the prediction of significant fibrosis was 0.688; this finding seems to be consistent with the data reported in the literature (20)(21)(22)(23)(24). The NPV of APRI in the prediction of fibrosis and cirrhosis was > 90% in a study by Guzelbulut et al and 92% in a study by Celikbilek et al (20,22).…”
Section: Discussionsupporting
confidence: 82%
“…Overall, the number of studies indicating a relationship between CDS and fibrosis staging is limited in CHB patients. While CDS was insufficient in the diagnosis of liver fibrosis in some studies, it could be used to diagnose fibrosis in several other studies (21,24,30). In the present study, the cut-off value and NPV of CDS for low and significant fibrosis in cirrhotic and noncirrhotic patients were > 5, 75.57%, and 97.42%, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…The other ones also showed that AUC of API was 0.767 and 0.529 for 3.5 and 5.5 cut off values, respectively (34,37). In this study, the AUC of API (0.861 for 5.0 cut off value) was higher than in other studies.…”
Section: U N C O R R E C T E D P R O O Fcontrasting
confidence: 51%
“…In a study published by Williams et al in 1988 (58), among 100 patients with HBV, the mean AST/ALT ratio was 0.59 in those without and 1.02 in those with cirrhosis respectively. However, Eminler and colleagues (59) found that the AAR performed inferiorly to other blood-based non-invasive algorithms in estimating the fibrosis stage in 237 HBV patients. Similarly, the ability of the AAR to diagnose significant fibrosis (F2-F4) was poor in a US cohort of 319 HBV patients (AUROC of 0.56) (60).…”
Section: Ast/alt Ratio (Aar)mentioning
confidence: 99%